2020
DOI: 10.3390/microorganisms8071035
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Molecular Identification of Brucella spp. in Camels in Egypt

Abstract: Brucellosis is one of the most important worldwide zoonoses of many countries including Egypt. Camel brucellosis has not gained much attention in Egypt yet. This study is focused on the three governorates with the highest camel populations and the largest camel markets in the country to determine the disease seroprevalence and identify the Brucella species in local camel holdings. In total, 381 serum samples were collected from male and female camels from Giza, Aswan, and Al-Bahr Al-Ahmar (the Red Sea) governo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 44 publications
(73 reference statements)
2
28
0
Order By: Relevance
“…Isolation of B. suis , B. melitensis, and B. abortus from livestock has been reported recently [ 8 , 9 ]. Brucella abortus and B. melitensis have also been isolated from humans, but B. suis has thus far only been identified in cattle, pigs, and camels [ 10 , 11 , 12 , 13 ]. Like in many other countries of the Mediterranean Basin, B. melitensis is the predominant Brucella spp.…”
Section: Introductionmentioning
confidence: 99%
“…Isolation of B. suis , B. melitensis, and B. abortus from livestock has been reported recently [ 8 , 9 ]. Brucella abortus and B. melitensis have also been isolated from humans, but B. suis has thus far only been identified in cattle, pigs, and camels [ 10 , 11 , 12 , 13 ]. Like in many other countries of the Mediterranean Basin, B. melitensis is the predominant Brucella spp.…”
Section: Introductionmentioning
confidence: 99%
“…Validation is the process that determines the fitness of a developed, standardized, and optimized assay used for the aim of diagnosis. Conventional PCR and RT-PCR have been used as a diagnostic tool in most of the published research for the detection of DNA of Brucella species in serum samples of small ruminants [19], camels [20,21], bovine [22][23][24], swine [25], and humans [26,27] without first being validated or validated in an accurate manner. Some authors have previously considered serum as the sample of choice for the same purpose [28].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the c-ELISA results, the individual seroprevalence of camel brucellosis in this study was estimated at 7%; this is the highest seroprevalence of camel brucellosis reported in Somalia. Despite the fact that there is no c-ELISA assay specifically validated in camels, the assay is widely used in the diagnosis of camel brucellosis [ 20 ]. Further, a study by Sayour et al (2015) suggests that c-ELISA is an excellent test for the detection of Brucella antibodies in camels, but needs further standardization in camel sera [ 21 ].…”
Section: Discussionmentioning
confidence: 99%